Interferon Treatment of Ehrlich Ascites Tumor Cells: Effects on Exogenous mRNA Translation and tRNA Inactivation in the Cell Extract - Sen, G. C. (1976)
We reported earlier that in cell extracts that were prepared from interferon-treated Ehrlich ascites tumor cells and preincubated and passed through Sephadex G-25 (S30(INT)), the translation of exogenous mRNA (viral and host) was impaired and the impairment could be overcome to a large extent by adding a crude tRNA preparation from Ehrlich ascites tumor cells but not from Escherichia coli. We find now that the rate of inactivation of some tRNA's (especially those specific for leucine, lysine, and serine) but not those of many others is faster in S30(INT) than in corresponding extracts from control cells. This increased rate of tRNA inactivation may perhaps account for the need for added RNA to overcome at least partially the impairment of translation in S30(INT). The relationship of the increased rate of tRNA inactivation to the antiviral effect of interferon is unclear. So far no significant difference has been detected in the amount of tRNA needed to overcome the impairment of encephalomyocarditis virus RNA translation in S30(INT) between tRNA from interferon-treated cells and tRNA from control cells. Furthermore, no difference was found in the rate of inactivation in S30(INT) between leucine-specific tRNA's from interferon-treated and from control cells. tRNA's specific for leucine and lysine were not inactivated (unless very slowly) during incubation under our conditions in an extract from interferon-treated (or from control) cells unless the extract had been passed through Sephadex G-25 or dialyzed. The translation of exogenous mRNA was, however, impaired in an extract from interferon-treated cells that had not been passed through Sephadex G-25. This impairment was apparently not overcome by added tRNA.